Evaluation of English Language Learning Programs on Universitas Subang by using CIPP Model - Ida Maulida; Muchlas Suseno; Syamsi Setiadi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to evaluate the English language teaching program integrated into the Mata Kuliah Karakter Unggul (MKKU) at Universitas Subang using the CIPP (Context, Input, Process, Product) evaluation model developed by Stufflebeam. Employing a descriptive qualitative approach, the study involved data collection through interviews, questionnaires, observations, and documentation. The findings revealed that the English program aligns well with the university’s character education framework and supports the development of students’ global competencies. The context evaluation indicated that students perceived strong alignment between the course content and the vision and mission of their study programs, as well as its relevance to future professional needs. The input evaluation showed that lecturers possess competencies aligned with their fields of expertise and that learning media were generally supportive, although digital media utilization remains inconsistent. The process evaluation highlighted improvements in students’ English proficiency, character formation, and readiness to face global challenges. The product evaluation confirmed positive outcomes in student engagement, character reinforcement, and oral communication confidence. Despite these strengths, students suggested improvements in speaking and listening activities, interactive learning methods, feedback mechanisms, and access to instructional resources. The study concludes that while the program is effectively structured, continuous enhancement in pedagogical strategies and infrastructure is essential to maximize its impact.